Special Purpose Entities in Megaprojects: Empty Boxes or Real Companies?. Issue 2 (April 2017) - Sainati, Tristano; Brookes, Naomi; Locatelli, Giorgio
Megaprojects involve organizations called "Special Purpose Entities" (SPEs) also known as "special purpose vehicles." Despite their relevance, particularly for governance, SPEs are under-investigated. In the project management literature, there is neither a widely accepted definition of SPEs nor a clear understanding of what it does. This article presents an extensive literature review, which considers three domains: legal, financial, and project management. Four outcomes are presented: the definition of SPE, the typology of existing SPEs, comparisons of existing SPEs, and descriptions of SPE uses in megaprojects.